Pelatihan dan Penyuluhan Pegunaan Tekhnologi Tepat Guna : Optimalisasi produksi di Usaha Briket Arang di Dampit Kabupaten Malang - Ery Yusnita; Irawan Setyabudi; Karunia Setyowati Suroto (Dharma: Jurnal Pengabdian Masyarakat, 2026)
The training program for the "Young Charcoal Briquette Farmers" business in Dampit District, Malang Regency, aims to optimize charcoal briquette production and quantity through training in the use of appropriate technology. This activity is motivated by the enormous potential of local biomass waste such as rice husks and coconut shells, which are utilized by local youth. However, the lack of modern technology is one of the obstacles to large-scale charcoal briquette production. The implementation method used includes theoretical counseling and hands-on training with demonstrations on the use of tools such as hammer mills, briquette presses, and drying ovens. The results of this activity show a 70% increase in charcoal production compared to normal, with more varied and better quality charcoal briquettes, and an increase in income of more than 50% / period compared to the previous production method, which still used conventional methods.